PEMBELAJARAN ETHNOMATEMATIKA GEOMETRI DENGAN MEMODELKAN KERAJINAN TRADISIONAL KIPAS BAMBU - Amirlita, Rizka (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Ethnomathematics is a field of study that combines mathematics with aspects of the culture and traditions of a particular society. In this context, bamboo fan crafts are one object that can be used as a mathematics learning medium, especially in geometry. This approach studies geometric concepts such as angles, symmetry, patterns, and proportion, while respecting local cultural heritage and traditions. Students can identify angles in fan designs, compare proportions between fan parts, and look for repeating angle patterns and try to describe the relationship between these angles. It is hoped that the results of this research will provide a deeper understanding of the relationship between mathematics and culture in the context of traditional bamboo fan crafts. Apart from that, this research can also provide new insights into the use of ethnomathematics in mathematics education.